RECIPROCAL: FINANCIAL REPORTING AGGRESSIVENESS - TAX REPORTING AGGRESSIVENESS AND CORPORATE GOVERNANCE - Dwi Handayani, Yenny; Ibrani, Ewing Yuvisa (Management Science Research Journal, 2023)
The research aims to explore the effect of financial reporting aggressiveness, tax reporting aggressiveness and corporate governance (CG). One manager is required to optimize the amount of profit earned from shareholders, one of which is by choosing various accounting policies that aim to produce financial reports with high profits. Tax planning activities by selecting accounting policies have a minimal impact on taxable income (taxable profit), as well as earnings management activities aimed at maximizing net income (accounting profit), both of which are reflected in the income statement. CG implementation is very important for a company, besides being able to reduce conflicts of interest between principals and agents, CG is an obligation that must be carried out by companies, so that the company's credibility in the public eye can be increased. Corporate governance can also limit the space for management to take aggressive tax actions and aggressive financial reporting. This study uses a quantitative method and the data used is secondary data with a sample of manufacturing companies listed on the IDX for the 2018-2020 period which was sourced on the official website of the Indonesia Stock Exchange. The results showed that the aggressiveness of financial reporting has a positive effect on the aggressiveness of tax reporting. Tax reporting aggressiveness has a positive effect on financial reporting aggressiveness, CG has no effect on financial reporting aggressiveness. CG Has no effect on the aggressiveness of tax reporting